Percutaneous endoscopic gastrostomy: Results of 115 cases - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2003)
Background/Aims: Percutaneous endoscopic gastrostomy is one of the gastrostomy methods used for patients who are unable to take food orally. We aimed to present our results for percutaneous endoscopic gastrostomy. Methodology: One hundred and fifteen patients undergoing percutaneous endoscopic gastrostomy by pull technique were retrospectively evaluated in terms of indications, complications, durability of tube, and mortality. Results: Of the 115 cases, 60 were males and 55 females with the median age of 67 (2-93) years. Indications for percutaneous endoscopic gastrostomy placement were cerebrovascular accident in 39, brain tumors in 24, subarachnoidal hemorrhage in 21, several neurologic disorders in 17, miscellaneous extra-cerebral tumors in 6, head injury in 5, hypoxic encephalopathy in 2, and iatrogenic in 1. The durability of the tube was a median of 242 (9-1988) days. The tube was removed in 16 patients and was changed in 11 patients with a median interval of 142.5 (35-427) and 133 (24-1251) days, respectively. Four wound infections, two buried bumper syndromes, and two aspiration pneumonias developed. Total follow-up was 114.1 patient-years with procedure-related mortality, 30-day mortality, and overall mortality of 0%, 3.5% (4/115), and 17.4% (20/115), respectively. The mortality rate was 45% for patients who had brain tumor and 11.6% for the remainder. Conclusions: Percutaneous endoscopic gastrostomy is a minimally invasive gastrostomy method with low morbidity and mortality rates, easy to follow-up, and easy to replace when clogged.
Keywords: percutaneous endoscopic gastrostomy; gastrostomy; enteral feeding; ANTIBIOTIC-PROPHYLAXIS; COMPLICATIONS; PEG